DOMINO GAMES IN LEARNING ARABIC - Endang Switri; Abdul Gafur; Zaimmuddin Zaimmuddin (Conciencia, 2020)
This research was conducted to find out the improvement of learning outcomes in grammar learning, Arabic by using domino card games. Participants in this study were odd semester students precisely seventh semester. The research was conducted from the results of child observers (students) following the qowa'idmaterial. This research method is a class action research. The steps of its implementation; there is planning, implementation, observation and reflection. The instruments are students. As a result of the implementation of this research that Arabic language learning results increased, students became enthusiastic in receiving learning, and educators were comfortable seeing the high learning spirit of learners.